Investigating Tourists' Revisit Proxies: The Key Role of Destination Loyalty and Its Dimensions. (September 2019) - Stylos, Nikolaos; Bellou, Victoria
Literature in tourism marketing has focused on understanding tourists' revisit patterns, mostly through its proxies (i.e., destination loyalty, past visitation, intention to revisit). Interestingly, however, consensus has not been reached yet, regarding not only the distinctiveness of these proxies but also their interrelationships. This study hypothesizes the impact of past visitation, along with holistic image and subjective norms, on tourists' intention to revisit directly, and via destination loyalty, expecting place attachment to serve as key moderator. Additionally, since research remains quite vague in terms of the destination loyalty components and their operationalization, this study tests other than the baseline model, a competing one, in which we replace destination loyalty construct with two of its main components, namely, destination commitment and intention to recommend. Evidence coming from 1, 292 British tourists visiting Crete, Greece, verifies the distinctiveness of the three proxies and identifies the superior explanatory power of the competing model.